2022
DOI: 10.2147/vhrm.s386791
|View full text |Cite
|
Sign up to set email alerts
|

Difference in GFAP Levels in POCD and Non-POCD Patients After on Pump CABG

Abstract: Introduction On-pump, coronary artery bypass grafting (CABG) is the most common cause of postoperative cognitive dysfunction (POCD) after cardiac surgery. Previous studies showed that the incidence of POCD after cardiac surgery was 60%, higher than non-cardiac surgery with 11.7%. Glial fibrillary acid protein (GFAP) is one of the sensitive biomarkers of brain damage. Previous studies have found that elevated GFAP serum is associated with cognitive impairment. This study aims to measure the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…In addition, GFAP is a protein that found in astrocytes and is released into the bloodstream following brain injury, and it has a high specificity and sensitivity of neurological damages 32 . Nurcahyo et al examined GFAP serum levels for patients with and without postoperative cognitive dysfunction (POCD) after on-pump coronary artery bypass grafting 35 . Their study showed that POCD patients had higher GFAP levels than non-POCD patients, which was consistent with our results in ELISA tests of GFAP levels in serum (Tables S7 , S8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GFAP is a protein that found in astrocytes and is released into the bloodstream following brain injury, and it has a high specificity and sensitivity of neurological damages 32 . Nurcahyo et al examined GFAP serum levels for patients with and without postoperative cognitive dysfunction (POCD) after on-pump coronary artery bypass grafting 35 . Their study showed that POCD patients had higher GFAP levels than non-POCD patients, which was consistent with our results in ELISA tests of GFAP levels in serum (Tables S7 , S8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurcahyo et al examined GFAP The correlation of TARV HP and relative difference of TAU protein between T2 and T1 for patients with C T1 -S100B > 115 pg/mL. T2-T1 relative difference between after and before surgery, T3-T1 relative difference between 12 h after and before surgery, T4-T1 relative difference between 24 h after and before surgery, T5-T1 relative difference between 48 h after and before surgery, HCA hypothermic circulatory arrest, ΔARV HCA the difference of average resistivity value before and after HCA phase, k HCA the slope of electrical impedance during HCA phase, MRAI abs maximum of the absolute value of resistivity asymmetric index, TARI abs absolute value of time integral of resistivity asymmetric index, TARV HP time integral of electrical impedance for half flow of perfusion; **means p < 0.01. www.nature.com/scientificreports/ serum levels for patients with and without postoperative cognitive dysfunction (POCD) after on-pump coronary artery bypass grafting 35 . Their study showed that POCD patients had higher GFAP levels than non-POCD patients, which was consistent with our results in ELISA tests of GFAP levels in serum (Tables S7, S8).…”
Section: Discussionmentioning
confidence: 99%